Increase in de novo food allergies after pediatric liver transplantation: Tacrolimus vs. cyclosporine immunosuppression. (26th August 2014) - Lebel, Marie‐Jeanne; Chapdelaine, Hugo; Paradis, Louis; Des Roches, Anne; Alvarez, Fernando
Abstract Post‐TAFA is an uncommon but serious complication of organ transplantation. This study aimed to compare the incidence of FA in CsA and tacrolimus‐treated children following OLT and identify risk factors. The medical charts of all patients who underwent OLT at our institution were reviewed. Between 1985 and 2010, 218 OLTs were performed on 188 pediatric recipients, of which 154 were included in the study. Three patients (3%) of the 102 receiving CsA developed FA, compared with nine (17%) in the 52 tacrolimus‐treated patients, the latter exceeding general population reported FA prevalence (RR 5.88; 95% CI: 1.66–20.81). All TAFA cases underwent transplantation before the age of three with an incidence of 29% (9/31) in the tacrolimus‐treated children in comparison with 7% (3/41) in the CsA group (RR 3.97; 95% CI: 1.17–13.45). Eosinophilia was present in 81% of children receiving tacrolimus compared with 54% in the CsA group (p = 0.002). We observed a statistically significant increase incidence of FA in tacrolimus‐treated children following an OLT and those under the age of three are particularly vulnerable. The underlying process is still unknown and probably multifactorial.